Influence of Rural to Urban Migration on Criminal Behaviour in Kaduna South, Kaduna State, Nigeria - Fakokunde, Mogbekeloluwa Olayinka; Shekwolo, David Markus; Akise, Ovie Oboathare; Kullah, David Hannatu (NIU Journal of Social Sciences, 2020)
The study investigated the influence of rural- urban migration on criminal behaviour in Kaduna South, Kaduna State. A case study and a survey design method was used with criminal report cases from Customary Courts and Police Area Command from 2010-2019 in Sabon Tasha and 176 participants who were selected using convenient sampling technique. Descriptive and inferential statistics of independent sample t- test, ANOVA, Chi- Square were used. Three hypotheses were stated in the study. Hypothesis one revealed a significant moderate rating of crime as a result of rural-urban migration in Kaduna South, X 2 (11) = 126.591, P < 0.01. The hypothesis was confirmed. Hypothesis two results of the t-test analysis revealed a statistically significant difference between male and female rural to urban migration of crime in Kaduna South, t(174)= 0.486, P > 0.05NS. In other words, the stated hypothesis was confirmed in this study.  Hypothesis three shows the mean and standard deviation scores of rural to urban migration of crime according to age where it revealed reveals a no statistically significant age difference of  rural to urban migration of crime for young and old people, F(2, 173) = 0.487, P > 0.05NS We concluded and recommended that, it is pertinent that, reasons for the increase in crimes in Nigeria includes unemployment/under-employment and urbanization which are increasing more widely and rapidly than improvement in the social and economic condition as such, functional social amenities such as electricity, pipe borne water should be provided in the rural areas. Keywords: Rural to Urban Migration and Criminal Behaviour